1980
DOI: 10.1172/jci109864
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in human mevalonate metabolism.

Abstract: A B S T R A C T (3,4). The further finding that the primary feedback control of cholesterogenesis is located at the site of mevalonate synthesis (5-8) has stimulated an intense interest in the metabolic fate of this cholesterol precursor. To date, two major metabolic pathways for circulating mevalonate have been documented in animals. The first, a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The studies of Kelly and Kratz have shown that increased mevalonate shunt activity does occur in SLOS patients, as they excrete significant amounts of 3-methylglutaconic acid (49). Other reports have shown that it is not unusual for the mevalonate shunt pathway to divert as much as 30-45% of mevalonate away from sterol synthesis (50)(51)(52)(53). Being female, sex hormones, fasting, and experimental diabetes increased the shunt activity by 30-35% (50-53).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The studies of Kelly and Kratz have shown that increased mevalonate shunt activity does occur in SLOS patients, as they excrete significant amounts of 3-methylglutaconic acid (49). Other reports have shown that it is not unusual for the mevalonate shunt pathway to divert as much as 30-45% of mevalonate away from sterol synthesis (50)(51)(52)(53). Being female, sex hormones, fasting, and experimental diabetes increased the shunt activity by 30-35% (50-53).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Pang et al (2008) also showed that the extract of I. paraguariensis decreased the blood and liver concentrations of lipids, as well as levels of glucose. Differences between males and females in the effect of I. paraguariensis on cholesterol levels may have been due to the females having double the renal capacity to convert mevalonate into CO 2 , compared to that of males, while the latter have an increased capacity to convert plasma cholesterol (Feingold et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Observations of circutlating mevalonate metalbolism in castratedn male rats and immatture female rats have impliedl that these sex differences are secondary to the effects of sex hormones (15). In humans, premenopausal femailes oxidize 68% more circulatinig mevalonate to CO2 than age-maitche(d imiales (16). Insulini-deficient, streptozotocin-treated rats also deinonstrate a marked reduction in shuint activity and an increase in sterologenesis (17 (12 uimlol in miiales an(I 21 nmol in femailes).…”
Section: Discussionmentioning
confidence: 99%
“…These sex differ-ences in the metabolism of circtulatinig mevalonate are dlue entirely to (liffereinces in renial metabolism (15). Recentlv, a sex differenice in circuilating mevalonate metalbolism has also l)eeni demonstratedi in humtiiianis; premenopautsal women oxidize 68% miiore eirculatinig mevalonate to CO2 thain age-matchedimales (16).…”
Section: Introductionmentioning
confidence: 99%